(untitled) (Editora Impacto Científico, 2025)
The objective of this research was to understand the production of meanings of health, illness and care, in the Family Health team (eSF), users of the USF and healers of Quilombo Jibóia, located in a municipality in the north of Bahia. Using a qualitative approach, centered on Discursive Practices, data collection occurred through 07 semi- structured interviews and analyzed through Dialogical Maps, highlighting the historical and social importance of blessing practices in the context of public health. The study contributes to rethinking health policies, promoting an equal dialogue between traditional and scientific knowledge, and expanding the understanding of the associated use of medicine and blessing. DOI: https://doi.org/10.56238/edimpacto2025.090-001